Advancing Green Urea Recovery Flow: Enhancing Efficiency Through Flow Conditioning to Control Turbulence and Pressure Drop - Saeful, Albarrobi Nabila; Saiful, Jusef; Fikri, Ahmad Atif (TURBO [Tulisan Riset Berbasis Online], 2025)
Green urea production requires high efficiency, in addition to reducing carbon emissions, high efficiency is needed to prevent waste from being wasted too much. High turbulence results in the creation of biuret that can interfere with the efficiency of urea production, one of the solutions that can be used to overcome this problem using flow conditioners. The analytical method is used to analyze and select the flow conditioner design, with the aim of having the most optimal turbulence and pressure drop values. The numerical method of Computational Fluid Dynamics (CFD) is also used in this study, the purpose of which is to validate the results and visualize the flow. The results show that the difference between the results of the analytical and numerical methods is not more than 5%, and the turbulence value can be reduced by about 5x by only losing about 0.3 bar of pressure from the system without the use of flow conditioners. This shows that the green urea production process can be more efficient and reduce the waste produced.